Optimization of Pulsed Saturation Transfer MR Fingerprinting (ST MRF) Acquisition Using the Cramér–Rao Bound and Sequential Quadratic Programming - Vladimirov, Nikita; Zaiss, Moritz; Perlman, Or (Magnetic resonance in medicine, 2025)
To develop a method for optimizing pulsed saturation transfer MR fingerprinting (ST MRF) acquisition. The Cramér-Rao bound (CRB) for variance assessment was employed on Bloch-McConnell-based simulated signals, followed by a numerical sequential quadratic programming optimization and basin-hopping avoidance of local minima. Validation was performed using L-arginine phantoms and healthy human volunteers at 3T while restricting the scan time to be less than 40 s. The proposed optimization approach resulted in a significantly improved agreement with reference standard values in vivo, compared to baseline non-optimized protocols (8% lower NRMSE, 7% higher SSIM, and 15% higher Pearson's r value, ). The combination of the CRB with sequential quadratic programming and a rapid Bloch-McConnell simulator offers a means for optimizing and accelerating pulsed CEST and semisolid magnetization transfer (MT) MRF acquisition.